THE EFFECTS OF WORK MOTIVATION IN MODERATING LEADERSHIP AND WORK TRAINING ON THE PERFORMANCE OF EDUCATIONAL STAFF IN PAYAKUMBUH STATE AGRICULTURAL POLYTECHNIC - Tun Huseno; Adrian Nasrun Putra (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2023)
This research aims to identify and analyze the influence of job training, leadership and work motivation on the performance of educational staff of Payakumbuh State Agricultural Polytechnic. Using the census method and a sample of 176 respondents of the entire educational staff at this college, this study is also intended to examine how work motivation moderates the relationship between leadership and job training on the performance of educational staff in this college. The analysis tool employed in this quantitative study is the Structural Equation Modeling (SEM) analysis method. The results of the study shows that leadership, job training and motivation had effects on staff performance of the Payakumbuh State Agricultural Polytechnic. However, work motivation did not moderate the relationship between leadership and job training on the performance of educational staff of the Payakumbuh State Agricultural Polytechnic. Keywords: leadership, job training, work motivation and performance